Electrochemical Properties of Ce0.5Sr0.5 (Co0.8Fe0.2)1−xZrxO3−δ Cathode Materials for Low Intermediate Temperature Solid Oxide Fuel Cells (LIT-SOFCs) Synthesized by Sol-Gel Method - Beyene Tesfaw Ayalew; P. Vijay Bhaskar Rao (Advances in Materials Science and Engineering)
Ce0.5Sr0.5 (Co0.8Fe0.2)1−x ZrxO3−δ (CSCFZ) powders were synthesized by the sol-gel method and characterized to study structural and electrochemical properties. X-ray diffractometer (XRD) patterns of all samples give nanosized particles of a high-degree crystalline cathode having a cubic-type perovskite structure of space group Pm-3m with the existence of oxygen vacancies in the lattices. The results have the perovskite phase with average crystallite sizes of 26.57 nm, 18.14 nm, 18.13 nm, and 18.12 nm with porosities of 9.93%, 9.87%, 9.50%, and 9.08% for x = 0, 0.1, 0.15, and 0.2, respectively. Scanning electron microscope (SEM) micrographs showed the presence of pores on the microstructure. Average grain sizes of prepared samples found from SEM images were in the range of 105.30–183.02 nm. The partial substitution of zirconium at the B-site shows more stable materials than the host without decreasing the porosity that much. The results of electronic conductivity analyzed by the four-probe dc technique show that the conductivity of synthesized materials increases with the increment of both dopant concentration and temperature by the decrement of area specific resistances. The electrical conductivity of CSCFZ steadily increased with the increment of temperature which reached 42.76 Scm−1 at around 450°C.